2010
DOI: 10.1210/me.2009-0439
|View full text |Cite
|
Sign up to set email alerts
|

Neural Crest-Specific Loss of Prkar1a Causes Perinatal Lethality Resulting from Defects in Intramembranous Ossification

Abstract: The cranial neural crest (CNC) undergoes complex molecular and morphological changes during embryogenesis in order to form the vertebrate skull, and nearly three quarters of all birth defects result from defects in craniofacial development. The molecular events leading to CNC differentiation have been extensively studied; however, the role of the cAMP-dependent protein kinase [protein kinase A (PKA)] during craniofacial development has only been described in palate formation. Here, we provide evidence that str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This data is consistent with our previously published work which suggests PKA is involved in differentiation and development in a number of cAMP responsive tissues (Jones et al, 2010; Nadella et al, 2008; Yin et al, 2008a). However, genes associated with thyrocyte terminal differentiation including, Thyroid Peroxidase , Thyroglobulin , and the Sodium-Iodide Symporter were all expressed at normal or even higher levels than WT in the R1a-TpoKO tumors (Supplementary Table 4).…”
Section: Resultssupporting
confidence: 94%
“…This data is consistent with our previously published work which suggests PKA is involved in differentiation and development in a number of cAMP responsive tissues (Jones et al, 2010; Nadella et al, 2008; Yin et al, 2008a). However, genes associated with thyrocyte terminal differentiation including, Thyroid Peroxidase , Thyroglobulin , and the Sodium-Iodide Symporter were all expressed at normal or even higher levels than WT in the R1a-TpoKO tumors (Supplementary Table 4).…”
Section: Resultssupporting
confidence: 94%
“…PRKAR1α encodes the cAMPdependent protein kinase (protein kinase A [PKA]) regulatory subunit type Ια and regulates neural crest development, migration, and differentiation during 45 The cranial neural crest cell originates in the ectodermal-neuroectodermal ridges of the cephalic neural folds, which subsequently undergo EMT and differentiate into most of the craniofacial structural components including the bones, nerves, connective tissue, and dentins in the embryonic stage. 46 Jones et al 47 reported that aberrant differentiation of neural crest mesenchymal cells resulted in CP. cAMP levels increase in the palate mesenchyme immediately before fusion of the palatal shelves, which is accompanied by increased PKA activation.…”
Section: Rt-qpcr Validationmentioning
confidence: 99%
“…Several tissue-specific KOs (neural crest, heart, pituitary, adrenal, thyroid) from the original Prkar1a loxp/lop line have now either been published or are near completion (Jones et al, 2010b; Yin et al, 2008a; Sahut-Barnola et al, 2010; Jones et al, 2010a; Yin et al, 2008b, 2008c). …”
Section: Mouse Studiesmentioning
confidence: 99%
“…However, it appears that β-catenin activation in R1α–deficient cells is an event preceded by yet unknown molecular abnormalities that take place within the still benign and R1α-haploinsufficient tissues in the early stages of tumor formation (Almeida et al, 2011b; Almeida et al 2012). The discovery that neural crest (Jones et al, 2010b), heart (Yin et al, 2008a), adrenal (Sahut-Barnola et al, 2010)-specific knockouts (KO) of R1α or other mice with R1α defects (Almeida et al, 2010; Tsang et al, 2010; Kirschner, et al, 2005; Griffin et al, 2004; Griffin et al, 2004; Pavel et al, 2008; Molyneux et al, 2010; Jones et al, 2010a), develop lesions caused by proliferation of stem cell-like TSPCs in adult tissues, such as the adult skeleton (Tsang et al, 2010; Pavel et al, 2008) was an important one that further supported the possible role of Wnt -signaling in R1α defects, since Wnt -signaling is critical for the maintenance and/or proliferation of pluripotential cells.…”
Section: Introductionmentioning
confidence: 99%